THE EMERGENCE AND EVOLUTION OF ARABESQUE AS A MULTICULTURAL STYLISTIC FUSION IN ISLAMIC ART: THE CASE OF TURKISH ARCHITECTURE - M. Arif Kamal, Murat Cetin (Journal of Islamic Architecture, 2011)
This paper elucidates the emergence and evolution of arabesque with specific reference to  the case of arabesque in Turkish art and architecture. It is argued here that arabesque is a fusion of styles rather than a pure and homogenous style. Furthermore, the paper aims to show that although the arabesque style appears to be a fanciful and freely organized manner of artistic treatment it is based on a very complex mathematical logic which is expressed through abstractionism. In this context, the grammar of geometry is elaborately used in the  implementation  of abstraction. Here, general characteristics as well as different modes or  types  of arabesque are discussed. Starting with the etymological roots of the term, the  history of its use in the literature  is  explored  through  the  paper. After  the  inquiry  of  its  material  and  pragmatic  aspects,  the development of the arabesque style is evaluated with regard to its transformations that took place along with its injection to Anatolia and mixing with Turkish culture. Finally, the morphological character of this fusion is put forward.   Keyword: Morphological character, geometry, fusion of styles, arabesque